SUN-533 Noninvasive, DXA-Derived Bone Structure Assessment of Acromegaly Patients - Kuzma, Martin; Vanuga, Peter; Sagova, Ivana; Pavai, Dusan; Jackuliak, Peter; Killnger, Zdenko; Binkley, Neil; Winzenrieth, Renaud; Genant, Harry; Payer, Juraj (Journal of the Endocrine Society, 2019)
Introduction: Impaired bone microarchitecture is involved in vertebral fracture (VF) development among acromegaly (AG) patients. Aim of the study : Comparison of DXA-derived bone parameters; areal BMD (aBMD), trabecular bone score (TBS) and 3D-SHAPER parameters in AG patients with healthy controls. Methods: This cross-sectional study evaluated acromegaly patients and a control group of healthy subjects. In all subjects a single measurement of pituitary axis hormone levels, bone turnover markers (BTMs), aBMD, (total hip [TH] and lumbar spine [LS]), TBS and 3D-SHAPER were performed. All subjects underwent DXA assessment of VF using the semi-quantitative approach. Results : 106 patients with acromegaly (mean age 56,6 years, BMI 30,2 kg/m 2 ) and 104 control subjects (mean age 54,06 years, 28,4 BMI kg/m 2 ) were included. After adjustment for weight, LS aBMD, TBS and TH trabecular volumetric BMD (vBMD) remained lower (p=0.0048, <0.0001 and <0.0001, respectively) while cortical thickness (Cth) at TH and Neck remained thicker (p=0.006) in AG patients compared with controls. The best multivariate model (Model 1) discriminating patients with and without AG included TBS, TH Trabecular vBMD and TH Cth parameters (all p<0.05). 22 VFs (13 AG subjects) were recognized. In these subjects after adjustment for age, FN aBMD, TH cortical sBMD and TH cortical vBMD remained significantly associated with the prevalent VF (OR= 2.69 [1.07-6.78], 2.84 [1.24-6.51] and 2.38 [1.11-5.10] for neck aBMD, TH Cortical sBMD and TH Cortical vBMD respectively. The AUCs were similar for each parameter in this model. Conclusions : AG patients, regardless of VF presence, have lower trabecular bone quantitative parameters, but those with VFs had decreased cortical density.